2018
DOI: 10.5433/1679-0359.2018v39n1p261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monensin sodium associative to virginiamycin and/or essential oils on the performance of feedlot finished steers

Abstract: Effect of monensin sodium associative to virginiamycin and/or essential oils on the performance of feedlot finished steersEfeito associativo da monensina sódica à virginiamicina e/ou óleos essenciais sobre o desempenho de novilhos terminados em confinamento respectively in the same weightings. The daily carcass gain and carcass overall gain were higher in associations MO+VI and MO+EO+VI and provided an average gain of 16.67 kg more compared to MO and MO+EO. In the parameters feed efficiency, dry matter intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The same result was reported by Rogers et al (1995), where there was an increase in animal performance without affecting the dry matter intake. Heker et al (2018), when evaluating the DMI of steers confined and supplemented with MO alone or MO combined with VM, also did not obtain any difference between treatments. Squizatti (2019) evaluated 5 cannulated cattle, adapted for 14 days and supplemented with MO alone (30 mg kg -1 ) or MO + VM (30 mg kg -1 + 25 mg kg -1 ) and found no differences in DMI corroborating the present experiment.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The same result was reported by Rogers et al (1995), where there was an increase in animal performance without affecting the dry matter intake. Heker et al (2018), when evaluating the DMI of steers confined and supplemented with MO alone or MO combined with VM, also did not obtain any difference between treatments. Squizatti (2019) evaluated 5 cannulated cattle, adapted for 14 days and supplemented with MO alone (30 mg kg -1 ) or MO + VM (30 mg kg -1 + 25 mg kg -1 ) and found no differences in DMI corroborating the present experiment.…”
Section: Resultsmentioning
confidence: 73%
“…The ADG found by the same author showed no synergy between the additives, remaining at 1.240 kg day -1 . Heker et al (2018) examined the performance of confined steers receiving MO combined with VM and/or essential oils and found that the ADG for treatment with MO was 1,329 kg day -1 versus 1,559 kg day -1 in the combination of MO and VM, these data are in line with data of the present experiment with 1,636 kg day -1 versus 1,799 kg day -1 of the average of the treatments receiving different doses of MO and VM, that is, the combination of these provided greater daily gain regardless of the dosage provided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier report, Benchaar et al [ 58 ] concluded that there were no interaction effects with the combination MON + EO (350 mg/day and 2000 mg/day, respectively) on productivity and ruminal fermentation in lactating dairy cows. More recently [ 59 ], an experiment was performed to evaluate the effects of supplemental MON (200 mg/day) alone or combined with EO (1500 mg/day) on angus steers consuming a silage-based diet. Steers that were fed with the MON + EO combination had lower ADG and feed efficiency than steers that received MON alone.…”
Section: Resultsmentioning
confidence: 99%
“…Monensin (MON) is an ion carrier antibiotic with the potential to regulate rumen fermentation and improve animal performance [12,13]. As an antimicrobial supplement, monensin has demonstrated its ability to enhance daily weight gain, feed conversion efficiency, proportion of lean meat, and area of the eye muscle in ruminant animals [14][15][16]. It occupies an important position in the animal husbandry industry and brings great convenience and economic benefits to people.…”
Section: Introductionmentioning
confidence: 99%